Andrology for the Clinician - Schill, Wolf-Bernhard.; Comhaire, Frank; Hargreave, Timothy B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Andrology for the Clinician consists of two parts: In Part One, the busy clinician can easily find the problem-orientated information he or she needs on such issues as * Male factor fertility problems * Male contraception * Male genital tract infection and tumours Part Two contains in-depth subject-orientated information and adds important scientific background information to the recommendations received in Part One. Several leading experts have contributed to this work, which has been extensively subedited by world-renowned editors to ensure a well-structured didactic design and homogeneous content. This outstanding book is of great value for all Urologists, Andrologists, Dermatologists, Endocrinologists, Gynaecologists, Reproductive Biologists, GPs, Gerontologists, Psychologists, Psychiatrists, Paediatricians and anyone else interested in the problems of male sex and constitution.
Andrology: Definition, Clinical Issues and Prevalence -- Layout and How to Use the Book -- General Considerations -- Evidence-Based Medicine in Reproductive Medicine and Andrology -- Economic Cost and Cost-Effectiveness -- Ethics of Reproductive Research and Treatment -- Human Tissue for Research -- Diagnosing and Solving Clinical Problems -- Gender Dysphoria -- Disorders of Sexual Differentiation -- Problem: Abnormal Pubertal Development -- The Consensus-Based Approach to Standardized Diagnosis and Management of the Infertile Male -- The WHO Recommended Diagnostic Flow Chart -- Implications of Multifactorial Aetiology in the Diagnosis and Management of Male Infertility -- Sexual Dysfunction and Male Fertility -- Reference Values of Semen Variables and Their Interpretation -- Normal Spermatozoa and Isolated Abnormalities of Seminal Plasma -- Immunological Causes -- Iatrogenic Causes of Abnormal Spermatozoa -- Systemic Causes of Male Infertility -- Congenital Disorders and Male Infertility -- Acquired Testicular Damage -- Cause: Varicocele -- Infection/Inflammation of the Accessory Sex Glands -- Endocrine Factors -- Oligo-Astheno-Teratozoo-Spermia with No Demonstrable Cause (Idiopathic O-A-T) -- Azoospermia -- Erectile Dysfunction -- Erectile Deformity, Including Peyronie$1 (Bs Disease -- Ejaculatory Dysfunction: Premature Ejaculation, Delayed Ejaculation, Anejaculation, Low-Volume Ejaculation, Retrograde Ejaculation and Painful Ejaculation -- Orgasm Dysfunction -- Abnormal Libido -- Sexual Deviation and Paraphilias -- Controversies Regarding Postvasectomy Management -- Vasectomy Reversal -- Male Contraception -- Traditional Methods -- Reproductive Tract Infections/Sexually Transmitted Diseases -- HIV Infection -- Testicular Torsion -- Blunt Testicular Trauma -- Penile Fractures -- Priapism -- Testicular Pain and Related Pain Syndromes -- Scrotal Benign Lesions, Epididymal Cysts, Epididymal Tumours -- Testicular Cancer, CIS, Microcalcifications, TNM Classification -- Penile Inflammations -- Penile Cancer -- Circumcision -- Benign Prostatic Hyperplasia and Prostatic Cancer -- Prostatitis -- Gynaecomastia and Benign Breast Hyperplasia Including Iatrogenic Causes -- Skin Diseases of the Male Nipple -- Male Breast Cancer -- Neuroendocrine Regulation of Testicular Function -- Male Ageing: Wear and Tear -- Organ Failure and Common Disease of the Ageing Male -- Rationale -- Anatomy and Histology of the Male Genital Tract -- Sexual Differentiation and Development -- Physiology of Spermatogenesis -- Physiology of Sexual Function -- Endocrine Regulation -- Immunology of the Testis and Excurrent Ducts -- Male Contributions to the Biology of Conception and Fertilization -- Disorders of Prenatal Sexual Development -- Endocrine Disorders and the Role of Hormone Disrupters -- Infection/Inflammation of the Male Genital Tract as Cause of Abnormal Spermatozoa -- Urethritis, Sexually Transmitted Diseases (STD), Acquired Immunodeficiency Syndrome (AIDS) -- Disorders of Blood Flow: Arterial and Venous/Sexual Dysfunction and Varicocele -- Effects of Lifestyle and Toxicants -- Influence of Systemic Diseases and Iatrogenic Factors on Sexual and Reproductive Functions -- Mechanisms of Pathogenesis of Uro-Genital Cancers -- History and Examination for Andrological Problems -- Semen Analysis and Sperm Function Tests -- Cytomorphological Semen Analysis -- Clinical Microbiology -- Hormonal Evaluation in Infertility and Sexual Dysfunction -- Tumour Markers in Andrology -- Technical Investigations Including Imaging Procedures: Doppler, MRI, PET, Echo for Tumours -- Technical Investigations Including Imaging Procedures: Colour Flow Doppler and Thermography for the Detection of Reflux in Varicocele -- Evaluation of Testicular Biopsy Samples from the Clinical Perspective -- Genetics and Male Infertility -- Tumour Genetics (Prostate/Testis/Penis) -- to Surgical Section -- Surgical Procedures in Andrology -- Vasectomy Technique -- Vasovasostomy and Vasoepididymostomy -- Nonsurgical Cure of Varicocele by Transcatheter Embolization of the Internal Spermatic Vein(s) with a Tissue Adhesive -- Hormonal Treatment of Infertility -- Hormonal Male Contraception -- Treatment of Gender Dysphoria -- Treatment of Sexual Dysfunction -- Therapeutic Options for Benign Prostate Hyperplasia (BPH) and Prostatic Cancer -- Partial Androgen Deficiency of the Ageing Male (PADAM) and Testosterone Supplementation: Use, Misuse or Abuse? -- Abuse of Androgens -- Exotic Hormones -- Anti-Ageing Nutrition and Food Supplements -- Nutriceuticals and Food Supplements in the Treatment of the Infertile Man -- Assisted Reproductive Techniques -- Cryopreservation of Spermatozoa and Testicular Tissue Including Autotransplantation of Germinal Epithelium -- Current Research and Future Prospects for Gene Therapy in Andrology -- Behavioural Therapy and Counselling -- Donor Insemination, Egg and Embryo Donation -- Aesthetic Andrology: Surgical Interventions -- Aesthetic Andrology: Skin Care for Men $1 (BMale Cosmetics and Cosmetic Dermatologic Procedures.s
Keywords: Medicine; Dermatology; Gynecology; Endocrinology; Reproductive medicine; Urology; Medicine & Public Health; Urology; Dermatology; Reproductive Medicine; Endocrinology; Gynecology; Electronic books